Pembinaan Ekonomi Kreatif Desa Wisata Tanjung Lanjut Dengan Mempertahankan Kearifan Lokal Melalui Badan Usaha Milik Desa - Zulgani; Faradina Zevaya; Etik Umiyati; Helen Parkhurst; Rahma Nurjanah (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
The village of Tanjung Lanjut possesses abundant natural resources and scenic beauty that are yet to be fully explored by external visitors. These potential assets include Lake Tangkas, where hanging trees, putat leaves, and the local tradition of "makan merawang" are found. The cool natural ambiance and untouched environment make Lake Tangkas in Tanjung Lanjut a pleasant tourist destination. However, the community's empowerment in promoting the tourism potential of Lake Tangkas and harnessing the village's creative economy based on local wisdom has not been fully maximized. Although efforts by the Village-Owned Enterprises (Bumdes) have been made to enhance the local community's income, there remain untapped opportunities for creative economy initiatives rooted in local wisdom. This article aims to foster the development of Tanjung Lanjut's community in utilizing the village's creative economic potential while preserving its local wisdom, as well as supporting the growth of the Tanjung Lanjut Village-Owned Enterprise in expanding the existing businesses through creative economy approaches based on local wisdom.